Ɑ-MnO2 nanowire induces cytotoxicity of human lung fibroblasts based on a 3D organotypic culture. (4th July 2019) - Li, Yan; Li, Jinquan; Wang, Yixin; Wang, Pengcheng; Gong, Zhiyong; Yang, Wu; Yang, Xu
Abstract: In this study, we performed a 3D organotypic culture of human lung fibroblast (HLF) in a microfluidic device. This 3D HLF model could partly simulate the biological responses of human lung. ɑ-MnO2 nanowires were successfully synthesized using the hydrothermal approach. Material characterization identified the existence of ɑ-MnO2 nanostructure. Based on this 3D organotypic HLF model, our results demonstrated that ɑ-MnO2 nanowires can induce cytotoxicity in dose-dependently. Because the accumulation of reactive oxygen species (ROS) and depletion of glutathione (GSH) are observed in the nanowire-treated cells. In addition, ROS generation induced intracellular increase of malondialdehyde (MDA), DNA damage and activated alpha-smooth muscle actin expression. Based on these results, we concluded that a mechanism for ɑ-MnO2 nanowire-induced pulmary toxicity, which involves the accumulation of ROS, up-regulation of oxidative stress and inflammatory factors. This investigation may provide a fundamental insight to understand the nanotoxicity of wire-shaped nanomaterials.